Tantalum, easy as Pi: understanding differences in metal–imido bonding towards improving Ta/Nb separations. Issue 23 (20th May 2022) - Weberg, Alexander B.; Chaudhuri, Subhajyoti; Cheisson, Thibault; Uruburo, Christian; Lapsheva, Ekaterina; Pandey, Pragati; Gau, Michael R.; Carroll, Patrick J.; Schatz, George C.; Schelter, Eric J.
Abstract : A selective separation of the critical metals tantalum and niobium was accomplished from π-bonding-based reactivity differences of imido complexes. New insights into Ta/Nb separations were gained through detailed kinetic and computational studies. Abstract : The separation and purification of niobium and tantalum, which co-occur in natural sources, is difficult due to their similar physical and chemical properties. The current industrial method for separating Ta/Nb mixtures uses an energy-intensive process with caustic and toxic conditions. It is of interest to develop alternative, fundamental methodologies for the purification of these technologically important metals that improve upon their environmental impact. Herein, we introduce new Ta/Nb imido compounds: M( t BuN)(TriNOx) (1-M ) bound by the TriNOx 3− ligand and demonstrate a fundamental, proof-of-concept Ta/Nb separation based on differences in the imido reactivities. Despite the nearly identical structures of 1-M, density functional theory (DFT)-computed electronic structures of 1-M indicate enhanced basic character of the imido group in 1-Ta as compared to 1-Nb . Accordingly, the rate of CO2 insertion into the MNimido bond of 1-Ta to form a carbamate complex (2-Ta ) was selective compared to the analogous, unobserved reaction with 1-Nb . Differences in solubility between the imido and carbamate complexes allowed for separation of the carbamate complex, and led to an efficient Ta/Nb separation ( S Ta/Nb = 404 ± 150) dependent on the kinetic differences in nucleophilicities between the imido moieties in 1-Ta and 1-Nb .